Subaerial oxidative uranium mobilization at the culmination of the Great Oxidation Event - Ann M. Bauer; Weiqiang Li; Kyle S. Rybacki; Eric E. Roden; Lee R. Kump; Clark M. Johnson (Proceedings of the National Academy of Sciences, 2025)
Redox-sensitive elements figure prominently in studies of the evolution of Earth’s surface redox state, including the first major rise in atmospheric O 2 , the Paleoproterozoic Great Oxidation Event. Most Precambrian rocks endured multistage tectonothermal histories, however, adding ambiguity to interpretation of their chemistry. Here, we apply U-Th-Pb isotope geochronology to the highly oxidized ~2.06 Ga Kuetsjärvi Volcanic Formation, Pechenga Greenstone Belt, Russia, to constrain the age and extent of U oxidation. By contrasting the relative mobility of U and Th using Pb isotopes, we find that complete to near-complete oxidation and removal of U occurred shortly after eruption. We argue that this likely indicates relatively high atmospheric O 2 , where oxidative weathering and alteration produced a global pulse of U to the oceans. Such a pulse could explain widespread shifts in the U-Th-Pb isotope character of mantle reservoirs at ~2 Ga, including a decrease in the 232 Th/ 238 U ratio of the mid-ocean ridge basalt source and inception of the high- 238 U/ 204 Pb (HIMU) source to ocean island basalts, underscoring the connections between the redox character of the Paleoproterozoic surface and deep Earth. Using 207 Pb- 206 Pb, 238 U- 206 Pb, 235 U- 207 Pb, and 232 Th- 208 Pb geochronology, ~2.06 Ga oxidative loss of U may be distinguished from reintroduction of U at ~1.8 Ga during regional metamorphism, as well as Pb loss during a Phanerozoic tectonothermal event. Our results therefore establish the complex history of redox-sensitive element behavior in the rocks, highlighting the fact that elemental abundances, by themselves, are unlikely to capture straightforward proxy information in rocks that have seen multistage geologic histories.